2021
DOI: 10.1007/s10554-021-02228-w
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation the relationship of left ventricular global longitudinal strain and laboratory parameters in discharged patients with COVID-19: a follow-up study

Abstract: Background : The novel coronavirus infection (COVID-19) disease has spread rapidly and posed a great threat to global public health. The laboratory parameters and clinical outcomes of the disease in discharged patients remain unknown. In this study, we aimed to investigate the laboratory and echocardiographic findings of patients with COVID-19 after discharge and the relation between left ventricular global longitudinal strain (LVGLS) and inflammatory parameters in discharged patients. M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Moreover, in accordance with other published studies [ 19 , 20 ], we found that disease severity does not influence the extend of LVGLS impairment. Although one study [ 21 ] demonstrated significantly lower LVGLS values after discharge only in the group with severe pneumonia, the fact that the study’s cut-off value of impaired GLS was < 16 (absolute values), may be the cause of this discrepancy. Consequently, it seems reasonable to conclude that patients who have recovered from Covid 19 might be at risk of myocardial injury regardless of the severity of the respiratory symptoms.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, in accordance with other published studies [ 19 , 20 ], we found that disease severity does not influence the extend of LVGLS impairment. Although one study [ 21 ] demonstrated significantly lower LVGLS values after discharge only in the group with severe pneumonia, the fact that the study’s cut-off value of impaired GLS was < 16 (absolute values), may be the cause of this discrepancy. Consequently, it seems reasonable to conclude that patients who have recovered from Covid 19 might be at risk of myocardial injury regardless of the severity of the respiratory symptoms.…”
Section: Discussionmentioning
confidence: 97%
“…Global longitudinal strain as assessed by echocardiography and CMR was within the normal range. This could suggest that the reduction in GLS seen at 3 months (26, 27) and 6 months (9) in those admitted to hospital with COVID-19 may have resolved 1 year following their acute disease. This could mean that the abnormal LV parameters recover at a slower rate, as compared to RV function (26).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to cardiac disease, there is currently a mixed picture as to the long-term sequela following COVID-19 infection. In patients who have previously been admitted due to COVID-19, global longitudinal strain measured by echocardiography, that expresses left ventricular longitudinal shortening in percentage, and is used to assess left ventricular systolic function, was reduced as compared to controls 6 months following discharge (9), whilst left ventricular ejection fraction (LVEF) was preserved, suggesting subtle left ventricular systolic dysfunction. This is reflected by cardiopulmonary exercise testing, as a recent study by Vonbank et al showed that patients having recovered from both mild-moderate and severe COVID-19 had cardiopulmonary exercise impairment 6 months following COVID-19, as compared to healthy controls (10).…”
Section: Introductionmentioning
confidence: 99%
“…There is a modest correlation between COVID-19 infection and both LV GLS and RV FWS (Tables S1 and S2). There have been several studies that have assessed the clinical and TTE parameters in patients with acute COVID-19 infection [19][20][21][22][23][24]. The risk factors for developing long COVID-19 are several, including asthma, obesity, age, sex (female), and cardiovascular There have been several studies that have assessed the clinical and TTE parameters in patients with acute COVID-19 infection [19][20][21][22][23][24].…”
mentioning
confidence: 99%
“…There have been several studies that have assessed the clinical and TTE parameters in patients with acute COVID-19 infection [19][20][21][22][23][24]. The risk factors for developing long COVID-19 are several, including asthma, obesity, age, sex (female), and cardiovascular There have been several studies that have assessed the clinical and TTE parameters in patients with acute COVID-19 infection [19][20][21][22][23][24]. The risk factors for developing long COVID-19 are several, including asthma, obesity, age, sex (female), and cardiovascular risk factors (hypertension, diabetes, etc.)…”
mentioning
confidence: 99%